155k views
4 votes
Show that: |A⃗ + B⃗ |² - |A⃗ - B⃗ |² = 4 A⃗.B⃗ .​

1 Answer

5 votes

Answer:

Taking LHS:-


{ | \overrightarrow{A} + \overrightarrow{B} | }^(2) - { | \overrightarrow{A} - \overrightarrow{B} | }^(2)


\boxed{ \mathsf{using \: \overrightarrow{a} . \overrightarrow{a} =  ^(2) }}


\implies { | \overrightarrow{A} + \overrightarrow{B} | }^(2) = (\overrightarrow{A} + \overrightarrow{B})(\overrightarrow{A} + \overrightarrow{B})


\mathsf{using \: distributive \: property \: of \: vector \: multiplication}

eqn 1:-


\implies \mathsf{ \overrightarrow{A} \overrightarrow{A}+\overrightarrow{A} \overrightarrow{B} + \overrightarrow{B}\overrightarrow{A} + \overrightarrow{B}\overrightarrow{B}}

same with the other one


\boxed{ \mathsf{using \: \overrightarrow{a} . \overrightarrow{a} = a^(2) }}


{ | \overrightarrow{A} - \overrightarrow{B} | }^(2) = (\overrightarrow{A} - \overrightarrow{B})(\overrightarrow{A} - \overrightarrow{B})


\mathsf{using \: distributive \: property \: of \: vector \: multiplication}

eqn. 2:-


\implies \mathsf{ \overrightarrow{A} \overrightarrow{A} - \overrightarrow{A} \overrightarrow{B} - \overrightarrow{B}\overrightarrow{A} + \overrightarrow{B}\overrightarrow{B}}

eqn. 1 - eqn. 2 :-


\implies \mathsf{ \overrightarrow{A} \overrightarrow{A}+\overrightarrow{A} \overrightarrow{B} + \overrightarrow{B}\overrightarrow{A} + \overrightarrow{B}\overrightarrow{B} - ( \overrightarrow{A} \overrightarrow{A} - \overrightarrow{A} \overrightarrow{B} - \overrightarrow{B}\overrightarrow{A} + \overrightarrow{B}\overrightarrow{B})}

after distributing the minus sign inside the braces AA and BB get canceled, while the other two add up.


\implies \mathsf{2 \overrightarrow{A}\overrightarrow{B} + 2\overrightarrow{B}\overrightarrow{A}}


\boxed{ \mathsf{\overrightarrow{A} \overrightarrow{B}= \overrightarrow{B}\overrightarrow{A}} }


\implies \mathsf{ 4\overrightarrow{A}\overrightarrow{B} }

LHS = RHS

Hence, Proved! =D

User Bunkar
by
5.9k points